Development of innovative hybrid sandwich panel slabs: Experimental results - Mastali, Mohammad (2015)
The authors appreciate the collaboration of the following labs: Civitest for developing DHCC materials, PIEP for conducting VARTM process (Eng. Luis Oliveira) and Department of Civil Engineering of Minho University to perform the tests (Mr. Antonio Matos and Eng. Marco Jorge).